NiTi‐Based Elastocaloric Cooling on the Macroscale: From Basic Concepts to Realization. Issue 8 (7th August 2018) - Kirsch, Susanne‐Marie; Welsch, Felix; Michaelis, Nicolas; Schmidt, Marvin; Wieczorek, André; Frenzel, Jan; Eggeler, Gunter; Schütze, Andreas; Seelecke, Stefan
Abstract: Solid‐state cooling is an environmentally friendly, no global warming potential alternative to vapor compression‐based systems. Elastocaloric cooling based on NiTi shape memory alloys exhibits excellent cooling capabilities. Due to the high specific latent heats activated by mechanical loading/unloading, large temperature changes can be generated in the material. The small required work input enables a high coefficient of performance. An overview of elastocaloric cooling from basic principles, such as elastocaloric cooling cycles, material characterization, modeling, and optimization, to the design of elastocaloric cooling devices is presented. Current work performed within the DFG (Deutsche Forschungsgemeinschaft) Priority Program SPP 1599 "Ferroic Cooling", which is focused on the development and realization of a continuously operating elastocaloric cooling device, is highlighted. The cooling device operates in a rotatory mode with wires under tensile loading. The design allows maximization of cooling power by suitable wire diameter scaling as well as efficiency optimization by implementing a novel drive concept. Finally, computer‐aided design (CAD) models of the discussed solid‐state air cooling device are presented. Abstract : Elastocaloric cooling is a novel approach for environmentally friendly, no global warming potential, high‐performance cooling . The state‐of‐the‐art for macroscale solutions is reviewed and a continuously operating device based on multiple tension‐loaded NiTi wires is analyzed, optimized, designed, modeled, and realized as a highly efficient demonstrator. Computer‐aided design (CAD) models of the discussed solid‐state air cooling device are presented.